Cálculo y selección de los principales elementos constitutivos de una picocentral hidroeléctrica para accionamiento de un sistema alterno de abastecimiento de agua de la Universidad Nacional de Loja. - Carrión Gualán, Jorge Rafael (2004)
The present work is about the research carried out with the objective to define an appropriate methodology for the design of a hydroelectric generation at short scale. It is also shown the logical sequence of the calculation and selection of its main components. The work is structured in three chapters. In the chapter one the theoretical mark and the methodology for calculation and selection of the main constituent elements of the hydroelectric generation are presented. In the second chapter the methodology is applied to calculate a pico hydroelectric, taking as data the waterfall and the flow generated by a tract of the gulch “El palmo” and the generated electric power is estimated for the analyzed hydraulic resource. In the third chapter it is presented the analysis of the aspects of installation, maintenance, environmental impact and technician-economic valuation of the whole work of implementation in the hydroelectric generation at low level, to feed electrically an alternating system of water supply for the Universidad Nacional de Loja.